2010
DOI: 10.1177/1545968310376758
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Applying Electrical Stimulation Is an Important Factor Deciding the Success Rate and Maturity of Regenerating Rat Sciatic Nerves

Abstract: A short delay in the onset of ES may improve the recovery of a severe peripheral nerve injury, which should be considered as a way of augmenting rehabilitative approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…It was discovered that introducing a seven-day incubation (delayed ES) period following cell seeding led to an increased rate of regeneration and resulted in enhanced maturity of the neural components within the growth conduit. 98 The number of myelinated axons that successfully grew across the 10 mm nerve gap was twofold greater in the delayed ES group than in the immediate ES group. 98 The same study also showed that the nerves were larger and the amount of blood vessels and revascularization was greater in the delayed ES group than in the immediate ES group.…”
Section: Effect Of Electrical Stimulation On Neuronsmentioning
confidence: 87%
See 1 more Smart Citation
“…It was discovered that introducing a seven-day incubation (delayed ES) period following cell seeding led to an increased rate of regeneration and resulted in enhanced maturity of the neural components within the growth conduit. 98 The number of myelinated axons that successfully grew across the 10 mm nerve gap was twofold greater in the delayed ES group than in the immediate ES group. 98 The same study also showed that the nerves were larger and the amount of blood vessels and revascularization was greater in the delayed ES group than in the immediate ES group.…”
Section: Effect Of Electrical Stimulation On Neuronsmentioning
confidence: 87%
“…98 The number of myelinated axons that successfully grew across the 10 mm nerve gap was twofold greater in the delayed ES group than in the immediate ES group. 98 The same study also showed that the nerves were larger and the amount of blood vessels and revascularization was greater in the delayed ES group than in the immediate ES group. 98 These accounts highlight the importance of temporal relationships in ES experimental design in the optimization of NGCs.…”
Section: Effect Of Electrical Stimulation On Neuronsmentioning
confidence: 87%
“…Previous studies have shown that electrical stimulation of regenerating nerves initiated at day 8 after nerve repair had significantly more axons than controls receiving no ES [22]. However, in this study, percutaneous ES was used on the animals, which may not have stimulated the transected nerves effectively.…”
Section: Introductionmentioning
confidence: 85%
“…Experimental approaches to enhance recovery have focused on transection and nerve gap injuries, variously investigating pharmacologic agents, 2 neurotrophic factors, 3 novel scaffolds, and conduits, 4 blockade of factors that inhibit regeneration, 5 cellular transplantation, 6,7 and electrical stimulation. 812 …”
mentioning
confidence: 99%